ABOUT HYPOALLERGENICITY: MEANS OF PERSONAL HYGIENE OF ORAL CAVITY FOR CHILDREN INCLINED ALLERGY - G.E. Afinogenov; A.V. Grosser; A.G. Umerenkov ("Paediatrician" Publishers LLC, 2007)
The article deals with the findings in the evaluation of the allergenic properties of «R.O.K.S.» lime toothpastes for infants under 3 and «R.O.K.S.» raspberry and strawberry toothpastes for children aged between 4 and 7 years old based on the adequate model of the animals with the contact dermatitis by means of the passive skin anaphylaxis. The authors proved that both toothpastes did not have any allergenic effect and may be recommended for application among children disposed to allergic reactions.Key words: hypo sensible toothpastes, children.